Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1371/journal.pone.0017808
|View full text |Cite
|
Sign up to set email alerts
|

TDP-43 Regulates Drosophila Neuromuscular Junctions Growth by Modulating Futsch/MAP1B Levels and Synaptic Microtubules Organization

Abstract: TDP-43 is an evolutionarily conserved RNA binding protein recently associated with the pathogenesis of different neurological diseases. At the moment, neither its physiological role in vivo nor the mechanisms that may lead to neurodegeneration are well known. Previously, we have shown that TDP-43 mutant flies presented locomotive alterations and structural defects at the neuromuscular junctions. We have now investigated the functional mechanism leading to these phenotypes by screening several factors known to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
104
2
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(116 citation statements)
references
References 47 publications
7
104
2
2
Order By: Relevance
“…Loss-of-function models in invertebrates and zebrafish have shown a wide range of defects, ranging from embryonic lethality to morphological and functional defects of the nervous system, vascular system, and muscle degeneration (27,31,(34)(35)(36)(37). In mammalian species, TDP-43 gene deletion leads to early embryonic lethality (38)(39)(40)(41).…”
Section: Significancementioning
confidence: 99%
“…Loss-of-function models in invertebrates and zebrafish have shown a wide range of defects, ranging from embryonic lethality to morphological and functional defects of the nervous system, vascular system, and muscle degeneration (27,31,(34)(35)(36)(37). In mammalian species, TDP-43 gene deletion leads to early embryonic lethality (38)(39)(40)(41).…”
Section: Significancementioning
confidence: 99%
“…This finding is novel and promising for a couple of reasons: for instance, it has been recently found that TDP-43 modulates the local translation of mRNAs at the synapse, thus participating in a complex regulation of synaptic strength [30,31]. Moreover, other recent findings have proven that the depletion of TDP-43 could cause locomotor deficits in Drosophila by affecting the synaptic function [28,32]. Interestingly, Shh seems to impact on synaptic plasticity by similar mechanisms, including the modification of the presynaptic terminal size, synaptic vesicle size, and postsynaptic currents [10,19,20,44].…”
Section: Discussionmentioning
confidence: 90%
“…For instance, it has been found that TDP-43 could be localized in the synapses, likely affecting the local RNA translation and acting as a neuronal activity-responsive factor [30,31]. Interestingly, TDP-43 could also have a role in the motoneuron synaptic function and plasticity [28,[32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, flies mutants for TBPH closely reproduce most of the phenotypes observed in ALS patients like decreasing viability, affected synaptic transmission, defective locomotion and also age-related progressive neurodegeneration (Ritson et al 2010;Hazelett et al 2012;Li et al 2010;Neumann et al 2006). Recently, it has emerged that TBPH interacts with the Futsch protein, the Drosophila homolog to human MAP1B (Godena et al 2011) (Fig. 4d).…”
Section: Roles In Neuromuscular Developmentmentioning
confidence: 82%
“…4d). A reduced interaction between TBPH and Futsch seems to be responsible for the alteration in the organization of synaptic microtubules (Godena et al 2011).…”
Section: Roles In Neuromuscular Developmentmentioning
confidence: 99%